2020
DOI: 10.1136/bmjopen-2020-040282
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical margin status on the survival outcome after surgical resection of gastric cancer: a protocol for systematic review and meta-analysis

Abstract: IntroductionGenerally, complete resection with cancer cell negative (R0) margin has been accepted as the most effective treatment of gastric cancer and positive resection (R1/R2) margin has been associated with decreased survival to varied degrees. However, the independent impact of microscopical positive (R1) margin on long-term survival may be confounded. No meta-analysis has worked at the association between R1 margin and outcomes of gastric cancer and the available evidence are scant. Therefore, we plan to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A retrospective study reported no significant influence of surgical margin width on recurrence risk for ICC [ 31 ]. Jiang et al performed a meta-analysis to explore the clinical value of surgical margin width on prognosis of ICC after resection [ 32 ]. Although their conclusions supported the notion that narrow surgical margins were detrimental to RFS, their study noted heterogeneity between groups, and they did not assess bias caused by other variables such as tumor diameter, number, and stage in subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported no significant influence of surgical margin width on recurrence risk for ICC [ 31 ]. Jiang et al performed a meta-analysis to explore the clinical value of surgical margin width on prognosis of ICC after resection [ 32 ]. Although their conclusions supported the notion that narrow surgical margins were detrimental to RFS, their study noted heterogeneity between groups, and they did not assess bias caused by other variables such as tumor diameter, number, and stage in subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…53 However, designing a prospective experimental trial on this topic would be difficult considering the concomitant ethical issues. 54 According to the plan in its protocol, 27 the present study should have enrolled both eligible RCTs and non-randomized studies (NRSs) and pooled the outcomes from these two types of studies. Abbreviations: OS, overall survival; 5-year OS rate, 5-year overall survival rate; CI, confidence interval; HR, hazard ratio; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent reviewers will assess the methodological quality/risk of bias of the included studies, and disagreements will be resolved by team discussion [ 23 ]. RCTs will be assessed for risk of bias with Cochrane Collaboration’s tool [ 24 ].…”
Section: Methodsmentioning
confidence: 99%